Beginning Android 2 - Murphy, Mark L. (Apress, 2012)
Thanks for your interest in developing applications for Android! Increasingly, people will access Internet-based services using so-called "nontraditional" means, such as mobile devices. The more we do in that space now, the more that people will help invest in that space to make it easier to build more powerful mobile applications in the future. Android is new—Androidpowered devices first appeared on the scene in late 2008—but it likely will rapidly grow in importance due to the size and scope of the Open Handset Alliance. And, most of all, thanks for your interest in this book! I sincerely hope you find it useful and at least occasionally entertaining.